Long-term Dextromethorphan Use and Acute Intoxication Results in an Episode of Mania and Autoenucleation. Issue 4 (July 2020) - Bernstein, Laura B.; Albert, David; Baguer, Carlos; Popiel, Maryann
Abstract : N/A: The pharmacologic and neuropsychiatric sequelae of long-term dextromethorphan use and acute dextromethorphan intoxication are reviewed in this case report. Dextromethorphan ingestion at the high end of toxicity, although rare, can cause violence to oneself and others, even in those previously without any history of such behaviors. In this article, the neuropsychiatric consequences of dextromethorphan toxicity are highlighted in a case report of a 37-year-old woman who had been using dextromethorphan for 5 years. She presented to a large urban emergency department in a psychotic and manic state after attempting autoenucleation. She reported to consult liaison psychiatry staff that she had taken a total of 1400 mg of dextromethorphan over the course of 3 days with intent to experience altered state of consciousness. Toxicology screens on admission did not reveal any other substances in her system. She had no formal psychiatric history and no history of mania, psychosis, or self-harm. To our knowledge, this is the first case of autoenucleation resulting from dextromethorphan-induced mania with psychotic features.